Three Key Sub-leaf Modules and the Diversity of Leaf Designs - Li, Le; Ma, Zeqing; Niinemets, Ülo; Guo, Dali (Frontiers in Plant Science, 2017)
Earth harbors a highly diverse array of plant leaf forms. A well-known pattern linking diverse leaf forms with their photosynthetic function across species is the global leaf economics spectrum. However, within homogeneous plant functional groups such as tropical woody angiosperms or temperate deciduous woody angiosperms, many species can share a similar position in the leaf economics spectrum but differ in other vital leaf traits, and thus function differently under the given suite of environmental drivers. How diverse leaves differentiate from each other has yet to be fully explained. Here, we propose a new perspective for linking leaf structure and function by arguing that a leaf may be divided into three key sub-modules, the light capture module, the water-nutrient flow module and the gas exchange module. Each module consists of a set of leaf tissues corresponding to a certain resource acquisition function, and the combination and configuration of different modules may differ depending on overall leaf functioning in a given environment. This modularized-leaf perspective differs from the whole-leaf perspective used in leaf economics theory and may serve as a valuable tool for tracing the evolution of leaf form and function. This perspective also implies that the evolutionary direction of various leaf designs is not to optimize a single critical trait, but to optimize the combination of different traits to better adapt to the historical and current environments. Future studies examining how different modules are synchronized for overall leaf functioning should offer critical insights into the diversity of leaf designs worldwide.